Results from a dietary survey in an Indian T2DM population: a STARCH study. Issue 10 (31st October 2014) - Joshi, Shashank R; Bhansali, Anil; Bajaj, Sarita; Banzal, Subodh S; Dharmalingam, Mala; Gupta, Shachin; Mukhopadhyay, Satinath; Shah, Parag R; Sahay, Rakesh; Sarkar, Swapan; Manjrekar, Pravin V; Rathod, Rahul T; et al.
Abstract : Objective: To assess the dietary total and complex carbohydrate (CHO) contents in type-2 diabetes mellitus (T2DM) participants in India. Setting: We enrolled 796 participants in this cross-sectional, single-visit, multicentre, two-arm, single-country survey. Participants were enrolled from 10 specialty endocrinology/dialectology centres from five regions of India. Participants: A total of 796 participants (Asian) were enrolled in this study (385, T2DM and 409, non-T2DM). Key inclusion criteria—male or female ≥18 years, diagnosed with T2DM ≥12 months (T2DM), and not on any diet plan (non-T2DM). Study outcome: Primary outcome was to find out the percentage of total energy intake as simple and complex CHO from total CHO. Secondary outcomes were to find the differences in percentage of total energy intake as simple CHO, complex CHO, proteins and fats between T2DM and non-T2DM groups. The percentage of T2DM participants adhering to diet plan and showing glycaemic controls were also examined. Results: The mean (SD) of total calorie intake per day (Kcal) was 1547 (610, 95% CI 1486 to 1608) and 2132 (1892, 95% CI 1948 to 2316), respectively, for T2DM and non-T2DM groups. In the T2DM group (n=385), the mean (SD) percentage of total energy intake as total CHO, complex CHO and simple CHO was 64.1±8.3 (95% CI 63.3 to 64.9), 57.0±11.0 (95% CI 55.9 to 58.1) and 7.1±10.8 (95% CI 6.0 to 8.2), respectively. The mean (SD) percentage of complex CHO intake from total CHO was 89.5±15.3 (95% CI 88.0 to 91.1). The mean (SD) total protein/fat intake per day (g) was 57.1 (74.0)/37.2 (18.6) and 57.9 (27.2)/55.3 (98.2) in T2DM and non-T2DM groups, respectively. Conclusions: Our study shows that CHO constitutes 64.1% of total energy from diet in T2DM participants, higher than that recommended in India. However, our findings need to be confirmed in a larger epidemiological survey. Trial registration number: NCT01450592 & Clinical Trial Registry of India: CTRI/2012/02/002398.